Issues on Development of Civil-procedural Mechanisms for the Protection of Individual Rights and Legal Interests in the Republic of Armenia - Hovhannisyan, V. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The primary role of justice is the protection of human rights and free- 72 doms as key social values that may not be achieved due to formal implementation of law. As a priority, civil procedural tools shall fully ensure the protection of human rights and freedoms as key social values strictly in line with conventional and constitutional requirements, qualities and perceptions. Effective legal protection tools and legality of procedural regulations can be ensured only through procedures compliant with general and special conventional and constitutional requirements and qualities. It should be noted that civil procedural tools of protection of rights shall be assessed by presumption of legality. Legal regulation or the fact of legally established type of proceedings are considered legal as long as the Constitutional Court of RA has not declared the civil procedural proceeding non-constitutional fully or partly, or European Court has not established the fact of violence of conventional provisions and requirements. The author takes the view that civil procedural proceedings of protection of rights are in dynamism, and the quality changes in different types of civil procedures are linked to development of law. And this necessity derives from the obligation of the state to ensure the realization of conventional and constitutional provisions. By the way, the dynamics of quality changes, according to the author, has exhausted the actuality of modern classification of the types of civil procedures. The author has come to the conclusion that realization of the conventional principle “living tool” not only conditions continuous elaboration and amendment of procedural proceedings and tools of protection of subjective interests in national legal system, but also predicts the main peculiarities of development of the civil procedure types and implication of differentiated forms according to the new legal perceptions.